Development of cross laminated timber-cold-formed steel composite beam for floor system to sustainable modular building construction. (August 2021) - Navaratnam, Satheeskumar; Widdowfield Small, Deighton; Gatheeshgar, Perampalam; Poologanathan, Keerthan; Thamboo, Julian; Higgins, Craig; Mendis, Priyan
Abstract: Cold-formed steel (CFS) and cross-laminated timber (CLT) structural components are widely employed in low- to mid-rise and modular building constructions. These two materials have individually shown to be lightweight, and possess relatively higher strength characteristics. Owing to these benefits, composite CLT-CFS sections can be used as structural elements and possibly be employed in modular buildings with enhanced structural performances. This paper presents the development of CLT-CFS composite beam for the floor system in modular buildings and investigates the structural performances through finite element (FE) analyses. Initially, the FE models of CFS beam and CLT panel were developed and validated with experimental results. Validated models were used to develop the FE model of CLT-CFS composite beam for the floor system. Results of FE analyses of the CLT-CFS composite floor systems showed that considerable benefits in terms of structural response can be achieved due to the mobilisation of composite action. For the CLT-CFS system investigated in this research, about 20% of enhancement in moment capacity was found. The presented study leads a path to highlight the gains in the structural performance of CLT-CFS composite beams floor system and it is a prospective option to be employed in sustainable modular building construction.